The effectiveness of homeopathy in relieving symptoms and reducing antibiotic use in patients with otitis media: A systematic review and meta-analysis - Rachel Perry; Alyson L. Huntley; Nai Ming Lai; Michael Teut; David D. Martin; Esther T. van der Werf (Heliyon, 2024)
Aim: This systematic review of clinical trial evidence aims to determine whether homeopathy can effectively relieve symptoms and reduce antibiotic use in patients diagnosed with otitis media (OM). Methods: Seven databases and four trial registries were searched. Eligible studies included randomised- and non-randomised-controlled-trials in patients diagnosed with OM. Studies on Individualised- and non-Individualised-Homeopathy (IH, non-IH) were included, and controls were inactive and/or active treatment. Primary outcomes were clinical-improvement and antibiotic-use. Data extraction, Risk of Bias and certainty of evidence (GRADE) were performed using established methodology. Results: Nine studies (IH = 4, non-IH = 5) comprising seven Randomised Clinical Trials (RCTs) and two non-RCTs (nRCTS) compared homeopathy with placebo (n = 2) or standard care (n = 7). 4/7 included RCTs reported statistically significant individual outcomes at relevant time points (symptom score, MEE, and antibiotic use) favouring homeopathy. However, heterogeneity of study designs, homeopathic interventions and outcome measures hindered the pooling of data for most outcomes, except for antibiotic use (non-IH). Add-on non-IH reduced filled antibiotic prescriptions by 46 % (RR = 0.54 [95%CI: 0.28, 1.06], P = 0.07, I2 = 12 %), but this did not reach statistical significance. Most studies demonstrated that the homeopathy group had less adverse events than the control group. Conclusions: The evidence base for the effectiveness of homeopathy and OM treatment is modest in study number, size, and risk of bias assessment. Individual RCTs report positive effects on clinical improvement and/or antibiotic use at relevant time points with homeopathy with no safety issues. Due to heterogeneity, the current evidence is insufficient to satisfactorily answer whether homeopathy is effective for clinical improvement and reducing antibiotic use in patients with OM. A Core Outcome Set for OM for future research is warranted to improve the potential for meta-analyses and strengthen the evidence base.